Plan de marketing para la empresa comercial Jácome”, cantón Quevedo, año 2015 - Elaje Arana, Jefferson Hernán (2015)
For this work a marketing plan that will help the business to capture more market Jácome de Quevedo which is running where he made a note that the means used are the press and television, the same was made budget was made For this work, marketing strategies, sales and economic were performed to ensure that the company achieves capture the market which is aimed at is very tentative. This legal research is divided into six chapters. In the first chapter, the main part for understanding the problem and the effect was treated, it was necessary to hypothesize that the solution to the problem was in compliance with the research hypothesis. The second chapter refers to the theoretical framework, aspects: referential, conceptual and legal. In the third chapter the methodology used in the investigation at issue described; the methods used, the types of research, people, samples of techniques and instruments used in data collection. In the fourth chapter the hypothesis is tested through the research results obtained by surveying residents Quevedo Canton, on Commercial Jacome and also supported the proposal of this research. After the proposal is done based on the objectives, description of the'propuesta, beneficiaries and social impact, etc. The fifth chapter describes the conclusions and recommendations. In the sixth chapter we find the literature that was used for scientific research. The seventh and final chapter are the appendixes. The fifth chapter describes the conclusions and recommendations. At the end we bibliography and appendices